GUI in VC++(6.0) for Creating OpenGL Objects and Animation - Prasad, J.Ravi Kiran (My University, 2007)
This project entitled "A GYU in VC++(6.0) for Creating OpenGL Objects and Animation" is developed for creating Opengl objects and animation. OpenGL is a high quality 3D graphics Application Program Interface. By using this OpenGL, high-quality still and animated 3-Dimensional color objects with graphic effects such as shading, lighting, texture mapping are created. OpenGL is a unique choice for creating these objects mainly because of it's portability and fast rendering features. The main focus is to provide necessary tools for drawing purposes and for viewing the developed model with various visualization effects like lighting, different views, dynamic rotation, dynamic pan, zooming option and so on. The GUI for creating these OpenGL Objects and animation, is developed in VC++(6.0).
Keywords: OpenGL objects; Three-D graphic applications; GUI; Graphic User Interface; Animations; Computer Science